A strategy of designed anionic metal–organic framework adsorbent based on reticular chemistry for rapid selective capture of carcinogenic dyes. (14th December 2021) - Feng, Meng; Wu, Liang; Wang, Xirong; Wang, Jingyu; Wang, Dongmei; Li, Chunxia
Abstract: In this work, highly effective and rapid removal of cationic carcinogenic organic dye molecules is achieved through the implementation of a novel anionic metal–organic framework (MOF). Benefit from reticular chemistry, an anionic pts topology‐directed MOF [CH3NH3][In (TPTAB)4]·solvents (In‐TPTAB, H4TPTAB = [1, 1′:3′, 1″‐terphenyl]‐4, 4′, 4″, 6′‐tetracarboxylic acid) has been solvothermally synthesized. The structural characteristics of high porosity and the large size 1D channel modified by uncoordinated O sites promote In‐TPTAB to be a promising adsorbent material. By ion exchange, In/Cu‐TPTAB exhibits obviously increased BET surface area (248 m2 g−1) compared with In‐TPTAB (55 m2 g−1). More importantly, In‐TPTAB presents commendable performances with the maximum adsorption capacities for toxic dye BR9 and MLB are up to 368 and 304 mg g−1, and the adsorption rates are 10.9 and 6.7 mg g−1 min−1, respectively. It is noteworthy that the high‐efficiency capacity of In‐TPTAB in capturing dyes surpasses many reported adsorbent materials. The mechanism of physical adsorption can be ascribed to the synergistic effect of multiple host‐guest interactions. Coupled with the good recyclable, push In‐TPTAB to be potential used for the removal of cationic organic pollutants Abstract : An anionic In‐TPTAB on the premise of pts topology‐directed has been designed and synthesized. The structural characteristics of high porosity and the large size 1D channel that modified by uncoordinated O sites. It is noteworthy that the high‐efficiency capacity of In‐TPTAB in capturing carcinogenic dyes BR9 and MLB surpasses many reported adsorbent materials.